ダイ41ジ ナンキョク チイキ カンソクタイ コウクウキ タイキ カンソク ホウコク 2000-2001 - 和田, 誠; ワダ, マコト; 猪原, 哲; イハラ, サトシ; 芝, 治也; シバ, ハルヤ; Wada, Makoto; Ihara, Satoshi; Shiba, Haruya (2001)
P(論文) 航空機を用いた大気観測を2000年2月17日から2001年1月19日まで, 第41次隊として実施した。昭和基地上空観測として9回, 内陸観測として, みずほ基地までの飛行をピラタス機16回(実際にはほとんどの飛行がZ40地点まで), セスナ機18回, MD210地点(昭和基地から約500km)までの飛行を1回, 実施した。昭和基地上空観測では, 二酸化炭素濃度の連続観測と高度7200mから900mごとに高度900mまでの8高度の空気の採取を, 内陸観測では, 機体搭載の機器による大気状態, エアロゾル数濃度の観測を, またドロップゾンデ観測システムによる緯度方向約150kmごとの大気状態の断面観測を, 実施した。 Aerosol, greenhouse gas, temperature, water vapor and wind observations in the atmosphere were carried out from 17 February 2000 to 19 January 2001 using aircraft around Syowa Station and along oversnow vehicle tracks between Syowa Station and Point MD210. Nine flights of the Pilatus PC-6 aircraft were conducted around Syowa Station, 16 flights of Pilatus PC-6 aircraft and 18 flights of the Cessna A 185F aircraft between Syowa Station and Mizuho Station, and one flight of the Pilatus PC-6 aircraft between Syowa Station and Point MD210. Continuous measurement of carbon dioxide concentration and air samplings using flasks were carried out from 7200m altitude to 900m altitude at 900m intervals around Syowa Station. Continuous observations of aerosol number density, temperature and water vapor were carried out along with dropsonde observations along the tracks every month except in the dark season. The dropsondes were launched at about 150km intervals along tracks. departmental bulletin paper